Super-amphiphobic nanofiber coating, coating and preparation method and application of super-amphiphobic nanofiber coating

By constructing ultra-double sprinkled nanofiber coating materials composed of base coating and surface coating, the problem of easy wear of existing ultra-double sprinkled materials is solved, the self-cleaning effect of liquid and solid particles is achieved, and good wear resistance and stability are achieved.

CN119709010AInactive Publication Date: 2025-03-28QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940454.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing super-double-sparing materials are easily worn during use, causing the coating to lose its super-hydrophobicity, limiting its scope of application.

Method used

The ultra-double sparse nanofiber coating material consisting of base coating and surface coating is used. The base coating has high adhesion and density. The surface coating has a low surface energy microstructure. The ultra-double sparse function is achieved by embedding the surface of the base coating.

Benefits of technology

It realizes the self-cleaning effect of liquid and solid particles, has certain wear resistance, and maintains stability and durability in various harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709010A_ABST
    Figure CN119709010A_ABST
Patent Text Reader

Abstract

The invention discloses a super-amphiphobic nanofiber coating, a super-amphiphobic nanofiber coating and a preparation method and application of the super-amphiphobic nanofiber coating, and belongs to the technical field of functional coatings. The super-amphiphobic nanofiber coating comprises a bottom layer component and a surface layer component, the bottom layer component comprises nanofibers, long-chain perfluorosilane and hydrophobic wax powder, and the surface layer component comprises nanofibers, long-chain perfluorosilane and tetraethyl silicate. Wherein the bottom layer coating has high cohesiveness and good compactness, the surface layer coating is used for preparing a super-hydrophobic surface with a low-surface-energy microstructure, and the surface layer coating is embedded into the surface of the bottom layer coating, so that the compactness stability of the bottom layer is ensured, and the super-amphiphobic functionalization of the surface layer is realized. Therefore, the super-amphiphobic nanofiber coating prepared by the invention can realize the amphiphobic function of liquid (water and glycerol), can prevent adhesion of solid particles, realizes the self-cleaning effect of liquid and solid, has certain wear resistance, and has stability and durability in various severe environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional coatings, and in particular relates to a super-amphiphobic nanofiber coating, a coating, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the increasing severity of environmental pollution and energy crisis, it is particularly important to develop nanofiber coating materials with super-amphiphobic properties. Super-amphiphobic coatings often refer to a class of low surface energy coatings with static water contact angles and static oil contact angles on the coating surface formed being greater than 150°. Super-amphiphobic materials can not only effectively prevent the self-cleaning function of the adhesion of liquid and solid particles, but also help to improve energy efficiency and extend the service life of materials. The preparation methods of super-amphiphobic materials currently provided include chemical vapor deposition, plasma process, sol-gel method, template method, laser etching, solid solution etching, electrochemical deposition, self-assembly method, etc., but there are some problems. Among these methods, only etching constructs roughness on the surface of the substrate, which limits its scope of application; other methods introduce micro / nanoparticles to produce roughness on the surface of the substrate. Fluorination is still the most commonly used modification method. However, the super-hydrophobic surface produced by conventional coating methods is easily worn during use. When the fluoride is worn, the hydrophilic substrate is exposed, causing the coating to lose its super-hydrophobicity. Therefore, it is of great significance to provide a new preparation method of nanofiber coating materials with super-amphiphobic properties. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a super-amphiphobic nanofiber coating, coating and preparation method and application thereof. The super-amphiphobic nanofiber coating material provided by the present invention is composed of a base coating and a surface coating, the base coating has high adhesion and good density, the surface coating prepares a super-amphiphobic surface with a low surface energy microstructure, and the surface coating is embedded in the surface of the base coating, which not only ensures the compactness stability of the base, but also realizes the super-amphiphobic functionalization of the surface.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In a first aspect, the present invention provides a super-amphiphobic nanofiber coating, comprising a bottom layer component and a surface layer component, wherein the bottom layer component comprises nanofibers, long-chain perfluorosilane and hydrophobic wax powder, and the surface layer component comprises nanofibers, long-chain perfluorosilane and tetraethyl silicate.

[0007] In the bottom layer component, the ratio of nanofiber, long-chain perfluorosilane and hydrophobic wax powder is (0.5-1 g):(2-4 mL):(0.5-1 g);

[0008] In the surface layer components, the ratio of nanofibers, long-chain perfluorosilane and tetraethyl silicate is (0.5-1 g):(3-6 mL):(1-2 mL);

[0009] The bottom layer component has an absolute dry weight of 0.5-3g / m 2 ;

[0010] The absolute dry weight of the surface component is 0.2-1g / m 2 .

[0011] Preferably, in the bottom layer component, the ratio of nanofibers, long-chain perfluorosilane and hydrophobic wax powder is 0.5g:3mL:(0.6-1g); in the surface layer component, the ratio of nanofibers, long-chain perfluorosilane and tetraethyl silicate is 0.5g:5mL:(1-2mL).

[0012] Preferably, the base coating has an absolute dry weight of 2-3 g / m 2 The absolute dry weight of the surface coating is 0.5-1g / m 2 .

[0013] In one or more embodiments, the nanofibers are selected from one or more of cellulose nanocrystals (CNC), cellulose nanofibers (CNF) and bacterial cellulose (BC).

[0014] Preferably, the particle size D50 (μm) of the nanofibers is 10-60 μm.

[0015] In one or more embodiments, the long-chain perfluorosilane is selected from one or more of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, trimethoxy(1H,1H,2H,2H-tridecafluorooctyl)silane, 1H,1H,2H,2H-perfluorododecyltriethoxysilane, trimethoxy(1H,1H,2H,2H-heptadecafluorodecyl)silane and 1H,1H,2H,2H-perfluorododecyltrichlorosilane.

[0016] In one or more embodiments, the hydrophobic wax powder is selected from one or more of palm wax powder, paraffin wax powder, polyethylene wax powder and stearic acid.

[0017] In a second aspect, the present invention provides a method for preparing a super-amphiphobic nanofiber coating using the above-mentioned super-amphiphobic nanofiber coating, comprising the following steps:

[0018] The nanofibers are added to an alkaline alcohol solution, long-chain perfluorosilane is added for fluorination modification, and hydrophobic wax powder is added for emulsification to obtain a primer;

[0019] The nanofibers in the alkaline alcohol solution are fluorinated by adding tetraethyl silicate and perfluorosilane to obtain a surface coating;

[0020] The bottom layer of paint is leveled on the surface of the substrate, dried until the water no longer flows, and then the top layer of paint is sprayed and dried to obtain a super-amphiphobic nanofiber coating.

[0021] In one or more embodiments, the bottom layer component has an absolute dry weight of 0.5-3 g / m 2 , preferably 2-3g / m 2 ; The absolute dry weight of the surface component is 0.2-1g / m 2 , preferably 0.5-1g / m 2 .

[0022] In one or more embodiments, the alkaline alcohol is alkalized with ammonia water, sodium hydroxide or sodium carbonate to adjust the pH to 10-11. Preferably, the alkaline alcohol is alkalized with ammonia water to adjust the pH to 10-11. Preferably, the alcohol is ethanol.

[0023] In one or more embodiments, the nanofibers are added into an alkaline alcohol solution, and the solid content of the nanofibers is 0.5-1 wt %.

[0024] In one or more embodiments, the fluorination modification is carried out by stirring the reaction at 40-50° C. in a closed environment for 8-12 hours.

[0025] In one or more embodiments, the emulsification temperature is 70-90° C., and the emulsification time is 1-5 min.

[0026] In one or more embodiments, the substrate includes soft and hard substrates, such as cotton fabric, sponge, metal, wood, paper, fiber, glass, plastic, etc., which can be coated.

[0027] In one or more embodiments, the drying temperature is 90-110° C., and the drying time is 20-60 min.

[0028] In a third aspect, the present invention provides the above-mentioned super-amphiphobic nanofiber coating.

[0029] The super-amphiphobic nanofiber coating comprises a bottom layer and a surface layer.

[0030] The super-amphiphobic nanofiber coating has a static contact angle of 157° to 170° to water, preferably 160° to 165°, a rolling angle of 3.5° to 5° to water, preferably 3.5° to 4.5°, a static contact angle of 153° to 160° to glycerol, and a rolling angle of 7.4° to 10° to glycerol.

[0031] After being worn 30 times, the static contact angle of the super-amphiphobic nanofiber coating to water is 153° to 166°, and the static contact angle to glycerol is 137° to 159°, preferably 152° to 160°.

[0032] Therefore, the super-amphiphobic nanofiber coating prepared by the present invention can achieve the adhesion of liquid (including hydrophobic and oleophobic) and solid particles, realize the self-cleaning effect of liquid and solid, and also has a certain wear resistance, as well as stability and durability in various harsh environments.

[0033] In a fourth aspect, the present invention provides applications of the above-mentioned super-amphiphobic nanofiber coating in the fields of marine antifouling, building protection, and textile materials.

[0034] One or some of the above technical solutions have the following advantages or beneficial effects:

[0035] (1) The super-amphiphobic nanofiber coating material constructed by the present invention is composed of a base coating and a surface coating, the base coating has high adhesion and good density, the surface coating prepares a super-amphiphobic surface with a low surface energy microstructure, and the surface coating is embedded in the surface of the base coating, which not only ensures the compactness stability of the base, but also realizes the super-amphiphobic functionalization of the surface. By adjusting the proportion of each component, the amphiphobic function of water and glycerol can be achieved, and it has a certain wear resistance.

[0036] (2) The base coating takes advantage of the high crystallinity and high density of the nanofibers after drying and film formation by utilizing the aspect ratio of the nanofibers. The surface energy of the coating is reduced by further fluorination modification, and then an emulsified coating made of hydrophobic wax powder is added to fill the pores between the nanofibers during the high-temperature drying process, further improving the density of the base coating. Tetraethyl silicate is also added to the top coating, which increases the surface roughness of the nanofibers and provides more fluorination-modified grafting sites for the nanofibers, as a super-phobic function of the low surface energy microstructure. The base coating is dried to remove most of the water and is no longer in a flowing state before the top coating is sprayed. The base coating has high adhesion, and the top coating is embedded in the surface of the base coating, which not only ensures the density and stability of the base, but also realizes the super-amphiphobic functionality of the surface.

[0037] (3) The super-amphiphobic nanofiber coating material provided by the present invention can not only effectively prevent liquid adhesion, but also has a self-cleaning function to prevent solid particles (biscuit crumbs or soil) from adhering.

[0038] (4) The super-amphiphobic nanofiber coating material provided by the present invention has a simple process, and a variety of combined materials with similar properties can be selected to prepare the coating, and it is suitable for curing and molding on the surface of various substrates, which provides a new idea for the preparation of super-amphiphobic nanofiber coating materials and has important guiding significance for the preparation of high-performance super-amphiphobic nanofiber coating materials.

[0039] (5) The super-amphiphobic nanofiber coating provided by the present invention has stable super-amphiphobic properties in various harsh environments (including ultrasonic washing (300W, 1h), sodium hydroxide solution immersion (pH=12, 5h), hydrochloric acid solution immersion (pH=3, 5h), hydrogen peroxide solution immersion (3% W / V, 5h), sodium chloride solution immersion (3% W / T, 3d), tetrahydrofuran immersion (5h) and ultraviolet radiation (18W, 5h)), and can be widely used in the fields of marine antifouling, building protection, textile materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0041] Figure 1 A schematic diagram of the process flow of the super-amphiphobic nanofiber coating in an embodiment of the present invention is shown;

[0042] Figure 2 This is a SEM image of the surface of the super-amphiphobic nanofiber coating prepared in Example 3 of the present invention;

[0043] Figure 3 This is a diagram showing the effect of the super-amphiphobic nanofiber coating prepared in Example 3 of the present invention in preventing solid particles from adhering;

[0044] Figure 4 These are the stability and durability test data of the super-amphiphobic nanofiber coating prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0046] Example 1

[0047] Reference Figure 1 The specific steps for preparing the super-amphiphobic nanofiber coating material are as follows:

[0048] (1) Take 0.5 g of cellulose nanofibers (CNF) from which excess water is removed by centrifugation, disperse them in 100 mL of ethanol and adjust the pH to 10 with aqueous ammonia, then add 3 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, seal and stir the reaction at 45 °C for 10 h, then heat the solution to 85 °C, add 0.6 g of palm wax powder and stir and emulsify for 3 min, and finally stir and cool at room temperature to obtain a base coating.

[0049] (2) 0.5 g of cellulose nanofibers (CNF) were centrifuged to remove excess water, dispersed in 100 mL of ethanol and adjusted to pH 10 with aqueous ammonia. Then, 5 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 2 mL of tetraethyl silicate were added and the mixture was stirred in a sealed state at 45 °C for 10 h to obtain a surface coating.

[0050] (3) Level the base coating on the surface of the substrate, with a dry weight of 1g / m 2 After drying at 105℃ until most of the water is removed and the product is no longer flowing, spray the surface coating with a spray gun. The absolute dry weight is 1g / m 2 , and continue drying at 105℃ for 30min.

[0051] Example 2

[0052] Reference Figure 1 The specific steps for preparing the super-amphiphobic nanofiber coating material are as follows:

[0053] (1) Take 0.5 g of cellulose nanofibers (CNF) from which excess water is removed by centrifugation, disperse them in 100 mL of ethanol and adjust the pH to 10 with aqueous ammonia, then add 3 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, seal and stir the reaction at 45 °C for 10 h, then heat the solution to 85 °C, add 0.6 g of palm wax powder and stir and emulsify for 3 min, and finally stir and cool at room temperature to obtain a base coating.

[0054] (2) 0.5 g of cellulose nanofibers (CNF) were centrifuged to remove excess water, dispersed in 100 mL of ethanol and adjusted to pH 10 with aqueous ammonia. Then, 5 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 2 mL of tetraethyl silicate were added and the mixture was stirred in a sealed state at 45 °C for 10 h to obtain a surface coating.

[0055] (3) Level the base coating on the surface of the substrate, with a dry weight of 2g / m 2 After drying at 105℃ until most of the water is removed and the surface is no longer flowing, spray the surface coating with a spray gun, and the absolute dry weight is 0.5g / m 2 , and continue drying at 105℃ for 30min.

[0056] Example 3

[0057] Reference Figure 1 The specific steps for preparing the super-amphiphobic nanofiber coating material are as follows:

[0058] (1) Take 0.5 g of cellulose nanofibers (CNF) from which excess water is removed by centrifugation, disperse them in 100 mL of ethanol and adjust the pH to 10 with aqueous ammonia, then add 3 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, seal and stir the reaction at 45 °C for 10 h, then heat the solution to 85 °C, add 0.6 g of palm wax powder and stir and emulsify for 3 min, and finally stir and cool at room temperature to obtain a base coating.

[0059] (2) 0.5 g of cellulose nanofibers (CNF) were centrifuged to remove excess water, dispersed in 100 mL of ethanol and adjusted to pH 10 with aqueous ammonia. Then, 5 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 1 mL of tetraethyl silicate were added and the mixture was stirred in a sealed state at 45 °C for 10 h to obtain a surface coating.

[0060] (3) Level the base coating on the surface of the substrate, with a dry weight of 2g / m 2 After drying at 105℃ until most of the water is removed and the product is no longer flowing, spray the surface coating with a spray gun. The absolute dry weight is 1g / m 2 , and continue drying at 105℃ for 30min.

[0061] Example 4

[0062] Reference Figure 1 The specific steps for preparing the super-amphiphobic nanofiber coating material are as follows:

[0063] (1) Take 0.5 g of cellulose nanofibers (CNF) from which excess water is removed by centrifugation, disperse them in 100 mL of ethanol and adjust the pH to 10 with aqueous ammonia, then add 3 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, seal and stir the reaction at 45 °C for 10 h, then heat the solution to 85 °C, add 0.6 g of palm wax powder and stir and emulsify for 3 min, and finally stir and cool at room temperature to obtain a base coating.

[0064] (2) 0.5 g of cellulose nanofibers (CNF) were centrifuged to remove excess water, dispersed in 100 mL of ethanol and adjusted to pH 10 with aqueous ammonia. Then, 5 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 1 mL of tetraethyl silicate were added and the mixture was stirred in a sealed state at 45 °C for 10 h to obtain a surface coating.

[0065] (3) Level the base coating on the surface of the substrate, with a dry weight of 2g / m 2 After drying at 105℃ until most of the water is removed and the surface is no longer flowing, spray the surface coating with a spray gun, and the absolute dry weight is 0.5g / m 2 , and continue drying at 105℃ for 30min.

[0066] Example 5

[0067] Reference Figure 1 The specific steps for preparing the super-amphiphobic nanofiber coating material are as follows:

[0068] (1) 0.5 g of cellulose nanofibers (CNF) from which excess water was removed by centrifugation were dispersed in 100 mL of ethanol and the pH was adjusted to 10 with aqueous ammonia. Then 3 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and the mixture was stirred and reacted at 45 °C for 10 h. The solution was then heated to 85 °C, and 1 g of palm wax powder was added and stirred and emulsified for 3 min. Finally, the mixture was stirred and cooled at room temperature to obtain a base coating.

[0069] (2) 0.5 g of cellulose nanofibers (CNF) were centrifuged to remove excess water, dispersed in 100 mL of ethanol and adjusted to pH 10 with aqueous ammonia. Then, 5 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 1 mL of tetraethyl silicate were added and the mixture was stirred in a sealed state at 45 °C for 10 h to obtain a surface coating.

[0070] (3) Level the base coating on the surface of the substrate, with a dry weight of 2g / m 2 After drying at 105℃ until most of the water is removed and the product is no longer flowing, spray the surface coating with a spray gun. The absolute dry weight is 1g / m 2 , and continue drying at 105℃ for 30min.

[0071] Example 6

[0072] Reference Figure 1 The specific steps for preparing the super-amphiphobic nanofiber coating material are as follows:

[0073] (1) 0.5 g of cellulose nanofibers (CNF) from which excess water was removed by centrifugation were dispersed in 100 mL of ethanol and the pH was adjusted to 10 with aqueous ammonia. Then 3 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane was added and the mixture was stirred and reacted at 45 °C for 10 h. The solution was then heated to 85 °C, and 1 g of palm wax powder was added and stirred and emulsified for 3 min. Finally, the mixture was stirred and cooled at room temperature to obtain a base coating.

[0074] (2) 0.5 g of cellulose nanofibers (CNF) were centrifuged to remove excess water, dispersed in 100 mL of ethanol and adjusted to pH 10 with aqueous ammonia. Then, 5 mL of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 1 mL of tetraethyl silicate were added and the mixture was stirred in a sealed state at 45 °C for 10 h to obtain a surface coating.

[0075] (3) Level the base coating on the surface of the substrate, with a dry weight of 3g / m 2 After drying at 105℃ until most of the water is removed and the product is no longer flowing, spray the surface coating with a spray gun. The absolute dry weight is 1g / m2 , and continue drying at 105℃ for 30min.

[0076] Embodiment 7:

[0077] The difference from Example 3 is that the cellulose nanofibers (CNF) are replaced by cellulose nanocrystals (CNC).

[0078] Comparative Example 1

[0079] The difference from Example 3 is that there is only a primer.

[0080] Comparative Example 2

[0081] The difference from Example 3 is that there is only a surface coating.

[0082] Comparative Example 3

[0083] The difference from Example 3 is that no palm wax powder is added.

[0084] Comparative Example 4

[0085] The difference from Example 3 is that the primer is not fluorinated.

[0086] Performance Testing

[0087] The relevant performances of the new model of the durable super-hydrophobic microstructure coating prepared by Examples 1 to 7 of the present invention were tested.

[0088] 1. Water and glycerol contact angle (CA) and rolling angle test: GB / T 30447-2013 nano film contact angle measurement method is used; wear resistance hydrophobic and oleophobic test: use a 200g weight to wear 30 times and then measure the contact angle. Among them, glass is used as the substrate and the test time is 10s.

[0089] Table 1 Basic properties of super-amphiphobic nanofiber coating material samples

[0090]

[0091]

[0092] As shown in Examples 1-7, the super-amphiphobic nanofiber coating material constructed by the present invention can realize the amphiphilic function of water and glycerol by adjusting the proportion of each component, and has certain wear resistance. As shown in Examples 1, 3 and Comparative Example 1, tetraethyl silicate provides a hierarchical microstructure for nanofibers in the surface coating, which is one of the conditions for realizing super-hydrophobicity. As shown in Example 3 and Comparative Example 2, since tetraethyl silicate also makes the coating structure loose while providing microstructure, the double-layer coating design can effectively overcome this defect. As shown in Example 3 and Comparative Example 3, the addition of palm wax further improves the tightness of the bottom coating, and improves the connectivity with the top coating. As shown in Example 3 and Comparative Example 4, the treatment of the bottom coating by a single palm wax cannot completely improve the hydrophilicity of the bottom coating, especially after wear, and this defect is clearly exposed.

[0093] 2. Test to prevent solid particles from adhering:

[0094] like Figure 3 As shown, the substrate coated with the super-amphiphobic nanofiber coating prepared in Example 3 is placed in a culture dish, tilted, and an appropriate amount of biscuit crumbs or sandy soil is added to the surface of the coating, and then water is added, and the biscuit crumbs or sandy soil will fall to the bottom together with the water. It is proved that the super-amphiphobic nanofiber coating prepared by the present invention has a self-cleaning function of preventing the adhesion of liquids and solid particles in addition to preventing the adhesion.

[0095] 3. Stability and durability test:

[0096] like Figure 4 As shown, the super-amphiphobic nanofiber coating material prepared in Example 3 was subjected to various stability and durability tests. The results show that after ultrasonic washing (300W, 1h), sodium hydroxide solution immersion (pH = 12, 5h), hydrochloric acid solution immersion (pH = 3, 5h), hydrogen peroxide solution immersion (3% W / V, 5h), sodium chloride solution immersion (3% W / T, 3d), tetrahydrofuran immersion (5h) and ultraviolet radiation (18W, 5h), it still maintains excellent super-amphiphobic protection, and its water contact angle is still greater than 150°.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A super-amphiphobic nanofiber coating, characterized in that: It comprises a bottom layer component and a surface layer component, wherein the bottom layer component comprises nanofibers, long-chain perfluorosilane and hydrophobic wax powder, and the surface layer component comprises nanofibers, long-chain perfluorosilane and tetraethyl silicate; In the bottom layer component, the ratio of nanofiber, long-chain perfluorosilane and hydrophobic wax powder is (0.5-1 g):(2-4 mL):(0.5-1 g); In the surface layer components, the ratio of nanofibers, long-chain perfluorosilane and tetraethyl silicate is (0.5-1 g):(3-6 mL):(1-2 mL); The bottom layer component has an absolute dry weight of 0.5-3g / m 2 ; The absolute dry weight of the surface component is 0.2-1g / m 2 .

2. The super-amphiphobic nanofiber coating according to claim 1, characterized in that: In the bottom layer component, the ratio of nanofiber, long-chain perfluorosilane and hydrophobic wax powder is 0.5g:3mL:(0.6-1g); in the surface layer component, the ratio of nanofiber, long-chain perfluorosilane and tetraethyl silicate is 0.5g:5mL:(1-2mL).

3. The super-amphiphobic nanofiber coating according to claim 1, characterized in that: The absolute dry weight of the base coating is 2-3g / m 2 ; The absolute dry weight of the surface coating is 0.5-1g / m 2 .

4. The super-amphiphobic nanofiber coating according to claim 1, characterized in that: The nanofibers are selected from one or more of cellulose nanocrystals, cellulose nanofibers and bacterial cellulose; Preferably, the particle size of the nanofibers is 10-60 μm; Preferably, the long-chain perfluorosilane is selected from one or more of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, trimethoxy(1H,1H,2H,2H-tridecafluorooctyl)silane, 1H,1H,2H,2H-perfluorododecyltriethoxysilane, trimethoxy(1H,1H,2H,2H-heptadecafluorodecyl)silane and 1H,1H,2H,2H-perfluorododecyltrichlorosilane.

5. The super-amphiphobic nanofiber coating according to claim 1, characterized in that: The hydrophobic wax powder is selected from one or more of palm wax powder, paraffin wax powder, polyethylene wax powder and stearic acid.

6. A method for preparing a super-amphiphobic nanofiber coating using the super-amphiphobic nanofiber coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: The nanofibers are added to an alkaline alcohol solution, long-chain perfluorosilane is added for fluorination modification, and hydrophobic wax powder is added for emulsification to obtain a primer; The nanofibers in the alkaline alcohol solution are fluorinated by adding tetraethyl silicate and perfluorosilane to obtain a surface coating; The bottom layer of paint is leveled on the surface of the substrate, dried until the water no longer flows, and then the top layer of paint is sprayed and dried to obtain a super-amphiphobic nanofiber coating.

7. The method for preparing the super-amphiphobic nanofiber coating according to claim 6, characterized in that: The alkaline alcohol is alkalized with ammonia water, sodium hydroxide or sodium carbonate to adjust the pH to 10-11; Preferably, the alcohol is ethanol; Preferably, the nanofibers are added to an alkaline alcohol solution, and the solid content of the nanofibers is 0.5-1 wt %; Preferably, the fluorination modification is carried out by stirring the reaction at 40-50°C in a closed environment for 8-12 hours; Preferably, the emulsification temperature is 70-90°C and the emulsification time is 1-5min; Preferably, the drying temperature is 90-110° C. and the drying time is 20-60 min.

8. A super-amphiphobic nanofiber coating obtained by the preparation method according to claim 6 or 7.

9. The super-amphiphobic nanofiber coating according to claim 8, characterized in that: The static contact angle of the super-amphiphobic nanofiber coating to water is 157°-170°, and the rolling angle to water is 3.5°-5°; the static contact angle to glycerol is 153°-160°, and the rolling angle to glycerol is 7.4°-10°.

10. Application of the super-amphiphobic nanofiber coating according to claim 8 or 9 in the fields of marine antifouling, building protection, and textile materials.